The Global Evolutionary History of Orf Virus in Sheep and Goats Revealed by Whole Genomes Data - Elisabetta Coradduzza; Fabio Scarpa; Angela Maria Rocchigiani; Carla Cacciotto; Giada Lostia; Mariangela Stefania Fiori; Yoel Rodriguez Valera; Alessandra Mistral De Pascali; Martina Brandolini; Ilenia Azzena; Chiara Locci; Marco Casu; et al. (Viruses, 2024)
Orf virus (ORFV) belongs to the genus Parapoxvirus (Poxviridae family). It is the causative agent of contagious ecthyma (CE) that is an economically detrimental disease affecting small ruminants globally. Contagious ecthyma outbreaks are usually reported in intensive breeding of sheep and goats but they have also been reported in wildlife species. Notably, ORFV can infect humans, leading to a zoonotic disease. This study aims to elucidate the global evolutionary history of ORFV genomes in sheep and goats, including the first genomes from Central America in the analyses. In comparison to the last study on ORFV whole genomes, the database now includes 11 more sheep and goat genomes, representing an increase of 42%. The analysis of such a broader database made it possible to obtain a fine molecular dating of the coalescent time for ORFV S and G genomes, further highlighting the genetic structuring between sheep and goat genomes and corroborating their emergence in the latter half of 20th century.